Evidence for Selection on Mitochondrial OXPHOS Genes in the Mediterranean Killifish IAphanius fasciatus/I Valenciennes, 1821 - Pappalardo, Anna Maria; Calogero, Giada Santa; Šanda, Radek; Giuga, Marta; Ferrito, Venera (Biology (Basel, Switzerland), 2024)
The old world killifish Aphanius fasciatus is a typical inhabitant of transition waters along the coasts of the central and eastern Mediterranean Sea, where it lives in environments (salt ponds, estuaries, and coastal lagoons) with large variations in salt, oxygen, and temperature. Therefore, A. fasciatus could be an interesting non-model species to be studied to evaluate the response of the mitochondrial oxidative phosphorylation (OXPHOS) genes to the variations and extremes of environmental factors. In this study, the sequences of three OXPHOS genes were analyzed in six populations of A. fasciatus to detect mutations and sites subject to selection. The results indicate that mutations were detected in two genes of the Greek population. Moreover, positively selected sites were also found. The information we obtained from the mitochondrial DNA sequences of A. fasciatus adds to the growing data on selective pressure acting on mitochondrial DNA. These results should be explored from the perspective of the local adaptation of a species highly tolerant to wide fluctuations of environmental parameters and should be supported using experimental evidence to better understand the interplay between historical climatic events and local adaptation and how each of them contributes to shaping the genetic structure of this species. Mitochondrial oxidative phosphorylation (OXPHOS) genes are a system subject to selection under determined environmental constraints despite a neutral evolution model that has long been hypothesized for the mitochondrial genome. In this study, the sequences of ND1, Cytb, and COI OXPHOS genes were analyzed in six populations of the eurythermal and euryhaline killifish A. fasciatus, to detect non-synonymous mutations leading to amino acid changes and to check whether selection acted on them using tests of recombination and selection. The results indicate a high COI and Cytb gene diversity and a high percentage of private haplotypes in all populations. In the Greek population, non-synonymous nucleotide substitutions were observed in the N-terminal region of COI and Cytb. Positively selected sites were also found. The information we obtained from the mitochondrial DNA sequences of A. fasciatus adds to the growing data on selective pressure acting on mitochondrial DNA in non-model species. These results should be explored from the perspective of the local adaptation of eurythermal and euryhaline species and supported using experimental evidence to better understand the interplay between historical climatic events and local adaptation and how each of them contributes to shaping the genetic structure of this species.